TRANSFORMASI PERILAKU BELANJA KONSUMEN DAN OMZET PEDAGANG PAKAIAN DI ERA ONLINE SHOP: STUDI KASUS DI KOMPLEK MMTC PANCING MEDAN - Atika Azwah Mrp; Ivana Paskanita Sidauruk; Rafina Wildaniah; Fahmi Fahreza; Nasirwan Nasirwan; Nabila Tijani Tharifah (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
The development of online shops has significantly changed consumer purchasing patterns and created challenges for clothing retailers. This research was conducted to examine changes in consumer shopping behavior and their implications for the revenue of clothing retailers in the MMTC Pancing Complex, Medan. A descriptive qualitative approach was employed in this study. Research data were obtained through interviews, observations, and documentation involving ten clothing store owners and ten consumers selected using purposive sampling. The collected data were analyzed using the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results show that online shops have influenced consumer behavior, particularly in searching for information, comparing prices, and making purchasing decisions. Consumers are increasingly attracted to online shopping because of its convenience, competitive pricing, promotional offers, and wider product variety. Furthermore, the presence of online shops has affected the sales performance and revenue of clothing retailers, although the impact varies among businesses. The study concludes that the growth of online shops has encouraged shifts in consumer behavior and required retailers to adopt adaptive strategies to sustain their businesses in the digital era.